2007
DOI: 10.1016/j.aquatox.2007.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Is the umbo matrix of bivalve shells (Laternula elliptica) a climate archive?

Abstract: Heavy metal accumulation into bivalve soft tissues has received increasing interest in recent years with respect to biomonitoring of environmental change including pollution. To a lesser extent, accretion of elements from the environment into bivalve hard structures (shells) has been investigated, although the importance of the shells as environmental archives has been acknowledged. Here we report element distribution within consecutive growth bands in the shells of the Antarctic soft shell clam Laternula elli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Nutrient (nitrate and phosphate) concentrations, as shown for both years 2010 and 2011 for both PC and AB, and as previously determined for the study area (Schloss and Ferreyra 2002), were not limiting phytoplankton growth; micronutrients such as iron (Fe) have been shown to abound in particles generated by subglacial erosion and thus Fe appears nonlimiting in the PC area (Dick et al 2007), as also generally observed in the region of the South Shetland Islands, which are sources of natural iron enrichment in the Antarctic Peninsula region (De Jong et al 2012). Phytoplankton cells might therefore grow and accumulate when physical conditions are adequate for it, although this has not been previously observed to the extent found in the present work.…”
Section: Discussionmentioning
confidence: 83%
“…Nutrient (nitrate and phosphate) concentrations, as shown for both years 2010 and 2011 for both PC and AB, and as previously determined for the study area (Schloss and Ferreyra 2002), were not limiting phytoplankton growth; micronutrients such as iron (Fe) have been shown to abound in particles generated by subglacial erosion and thus Fe appears nonlimiting in the PC area (Dick et al 2007), as also generally observed in the region of the South Shetland Islands, which are sources of natural iron enrichment in the Antarctic Peninsula region (De Jong et al 2012). Phytoplankton cells might therefore grow and accumulate when physical conditions are adequate for it, although this has not been previously observed to the extent found in the present work.…”
Section: Discussionmentioning
confidence: 83%
“…However, other factors such as increased input of lithogenic particles from underneath melting glaciers and from eroding land surfaces during the austral summer (Ahn et al, 1997;Klöser et al, 1994;Yoo et al, 1999) are bound to primarily affect the sub-littoral limpet fauna in the coastal environment of this volcanic archipelago (Ahn et al, 2002). Plumes of volcanic rock sediments carry high concentrations of heavy metals including Fe, Al, Cu and Zn into the nearshore waters of the South Shetland Archipelago Dick et al, 2007), and similar phenomena are described from areas along the maritime AP (Dierssen et al, 2002). Once taken up by sedimentary grazers or benthic filter feeders, these metals can exacerbate oxidative stress in animal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Dick, Philipp, Kriews, & Abele (2007) detected a faster growing and respiratory rate in younger individuals than older ones of other bivalves, with higher accumulation of heavy metals in their shells during polymerization. This shows a less discrimination between wanted and unwanted material in younger individuals.…”
Section: Discussionmentioning
confidence: 99%